Kajian Pelaksanaan Alokasi Dana Desa Di Kabupaten Kutai Kartanegara - Heru Suprapto (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2015)
Study of the implementation of the Village Fund Allocation (ADD) in Kutai Kartanegara Regency is an analysis using yurisis normative approach. The purpose of this study was to Know and analyze the successful implementation of ADD and analyze the impact of ADD to the improvement of public infrastructure, employment and empowerment of communities and village institutions. The results showed that the Quality of Planning , Implementation, Control Activities, Accountability Reporting is good and Respondents from LPM is not a good understanding of the regulations or policies associated with ADD and ADD are indicators of success can not be measured.